Reactions of metal-complexed carbocyclic 4π systems - Gleiter, Rolf; Werz, Daniel B. (Organometallics, 2005)
A plethora of different reactions on metal-complexed cyclobutadienes and cyclopentadienones are reviewed. The generation and chemistry of free 4π systems as well as substitution reactions on the carbocyclic cores and isomerization and ring enlargement reactions are the focus of interest.